Santri Cooperatives (Kosan) as a Means of Realizing Economic Empowerment and Independence of Santri - Dyah Syahira Tara Dewi; Aulia Rahma Diniya Putri (MONETARIUM: Journal of Economics Business and Management, 2024)
A new initiative called Koperasi Santri (Kosan) aims to help santri gain financial strength and become independent in Islamic boarding schools. The purpose of this study is to see how the santri cooperative functions as a way to encourage economic empowerment and independence of santri. This research uses a qualitative method by conducting in-depth interviews with cooperative administrators, santri, and Islamic boarding school managers. Participatory observation was also used to collect data, which allowed for a better understanding of the way the cooperative program is implemented in the Islamic boarding school environment. The results show that the Santri Cooperative (Kosan) has an important role in helping santri become more financially independent. By providing them with access to various financial services, entrepreneurship training, and the opportunity to provide financial coaching, the cooperative has built awareness of the importance of financial management and business development among santri.